National prevalence and associated factors of khat chewing among students in Ethiopia: A protocol for a systematic review and meta-analysis - Wondale Getinet; Tadele Amare; Wubet Worku (AOSIS, 2018)
The existing prevalence of khat chewing among university students ranges from 23.1% to 74.1%. Its impact affected students mentally, physically, economically and their social interaction. The aim of this systematic review and meta-analysis will be to determine the prevalence of khat chewing and associated factors among students in Ethiopia and to help guide policy makers in the decision-making process. A complete systematic review and meta-analysis of published studies on the prevalence of khat chewing and associated factors in Ethiopia will be conducted. A computerized internet search using Medline/PubMed, Google Scholar and EMBASE databases and reference lists of previous prevalence studies and full search strategy and cross-checking of reference lists of published peerreviewed articles will be conducted to identify all cross-sectional and cohort studies published in English. We will use the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) statement for reporting. Pooled estimated effect of prevalence of khat chewing and associated factors will be analyzed using the random effects meta-analysis (random effects model) and (with 95% CI) will be measured. The underlying work is based on systematic reviews of published data and thus do not require ethical review approval. The results of the systematic review will be disseminated in different conferences, seminars and published in a reputable international reviewed journal. A complete systematic review and meta-analysis of published studies on the prevalence of khat chewing and associated factors in Ethiopia will be conducted. All observational studies of (cross-sectional, cohort, case control) and randomized controlled trials will be included. A widespread range of studies and settings will be included.